Determining the Effectiveness of CBNAAT in the Diagnosis of Extrapulmonary Tuberculosis - Shivprasad Kasat; Mahendra Biradar; Ashish Deshmukh; Sunil Jadhav; Hafiz Deshmukh (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aims to determine the effectiveness and reliability of CBNAAT in the diagnosis of extra pulmonary tuberculosis (EPTB) cases in comparison to AFB smear. Tuberculosis is still a major public health issue around the world. Mycobacterium tuberculosis is thought to infect one-third of the world’s population. The two types of clinical manifestation of tuberculosis (TB) are pulmonary TB (PTB) and extrapulmonary TB (EPTB). While pulmonary tuberculosis is most common presentation, extrapulmonary tuberculosis is also an important clinical problem. Diagnosing extrapulmonary tuberculosis continues to be a challenge due to the paucibacillary nature of the samples collected from inaccessible sites and variable clinical presentation of the disease. Various direct and indirect methods of testing are available for diagnosing extrapulmonary tuberculosis accurately. Two of these tests which are routinely performed and are easily accessible are AFB smear and CBNAAT. AFB smear test is a method of visualization of acid-fast bacilli under microscope whereas CBNAAT is a cartridge-based nucleic acid amplification test that has long been used to diagnose pulmonary tuberculosis (PTB). The study is a retrospective descriptive study conducted at MGM Hospital Aurangabad, Maharashtra, India. The study used data from January 2017 to July 2018. Data from 166 patients with probable extrapulmonary TB were obtained. The efficacy of CBNAAT in the diagnosis of EPTB was compared to that of AFB smear. AFB smear and CBNAAT were performed on samples taken from 166 suspected EPTB patients. Lymph node, pus, pleural fluid, tissue, CSF, gastric lavage, cystic fluid, peritoneal fluid, ascitic fluid, colonic fluid, synovial fluid, and urine samples were collected. In AFB smear results, 17 cases were positive for TB bacilli while 149 tested negative. In the CBNAAT results, 25 cases were positive for TB bacilli whereas 141 tested negative. Eight cases were AFB smear negative but CBNAAT positive in a comparison examination. The simplicity and quick response time of CBNAAT make it a valuable tool for diagnosing EPTB cases. For the diagnosis of cases with EPTB, CBNAAT is more useful than AFB smear. However, other diagnostic tools should be taken into consideration along with CBNAAT for better diagnostic yield overall.